Stress analysis of finger joint subjected to tensile loading / Marzuki Ibrahim - Ibrahim, Marzuki (1998)
The project covers the Finite Element Analysis of glued wood joint under tensile loads with different tip thickness and lap length. The analysis of the wood joints will cover the mini finger joint. The sample sizes analysed in the study are varied from tips thickness (t) 0.6mm, 0.1mm, 0.8mm, 1.7mm, 1.75mm, 2.0mm, 0.6mm, 0.8mm, 1.0mm 0.1 mm.The specimens of tensioned glued finger joint are modelled using element type of Plane42 and Beam3 as stated in the ANSYS program. The computer output are analysed to determine the strength at t/P and L/P ratios. The maximum displacement are analysed and the plot of Load - Displacement are tabulated. It is find out that the lower t/P and the higher L/P ratio given better result.